Penerapan Metode Simple Moving Averange Dalam Memprediksi Produksi Ikan Nila - Abd Rahmat Karim Haba (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2022)
Production in each month is uncertain which will have an impact on the price of buying and selling of tilapia and the income of fishing communities in particular. The Department of Maritime Affairs and Fisheries is also still difficult to process production data and lack of information about production so that it cannot predict the production of tilapia in the future, The purpose of this study is to design a prediction system and to determine the error rate in predicting tomato production using the Moving Average method. The result of the error rate in making predictions is 0,36 % by using the MAPE method testing.